(In)Visibilidade literária na escola: literatura e cinema em destaque - Juliana Condé Rocha (2024)
This work presents the relevance of reading literary texts in elementary school II with the aim of stimulating the formation of readers (Lajolo; Zilberman, 2019) and critical spectators (Eiterer, 2008), and, consequently, to generate circles of belonging (Petit, 2009) cognitive and affective, with literature as a universal need and human right (CÂNDIDO, 2011). The research investigates how the development and application of a didactic proposal that includes the reading of a best-seller aimed at young audiences at school and the screening of its respective film adaptation can encourage the formation of regular readers and critical spectators. The work is justified by the development of literary (Cosson, 2009) and cinematographic (Eiterer, 2008) literacy practices at school. The proposal is based on the study of the compositional structure and the theme of the book and film The Advantages of Being Invisible, by Stephen Chbosky, which deal with delicate themes (Paiva, 2008), but necessary, such as those related to mental health and human existence. The use of both media allows the exploration of intertextual, interdiscursive and intersemiotic resources. The proposed activities are based on the basic sequence (Cosson, 2009); in the reading circle (Cosson, 2014, 2021) with a scheduled break (Dell’Isola, 2001) to read the book; in the intersemiotic study (Santaella, 1983) of the soundtrack (Sekeff, 2007) and, also, of the construction of literary and audiovisual narratives (Duarte, 2002). The results showed students' engagement in the reading process with an emphasis on the readers' autonomy, with them being protagonists in the discussion of the book and promoting an open space to approach sensitive topics, through the assimilation of the students' own universe with that covered in the book. Furthermore, the creation of a playlist as a soundtrack stands out, covering moments and situations experienced in the book and in the students' lives related to the work, and also the development of the epistolary genre through the proposal to write letters to the book's protagonist.